Poti in stranpoti nomotehnike - analiza nekaterih aktualnih primerov - Vezjak, Karmen (Pravni letopis, 2014)
Legal certainty bases on clear, unambiguous, understandable regulations that are perfectly legally drafted, and which - in advance - define the everyone's position, rights and obligations. The regulations that are correct with regard to the rules of legal drafting and base on the use of unified legal drafting rules are an important constituent element of legal certainty in a state governed by the rule of law. The importance of the quality of drafting of legislation is often underestimated. Even if sometimes different drafting solutions are possible, the adequacy, appropriateness and correctness of the legislation may not be affected by using different legal drafting techniques. The purpose of this article is to examine, whether and how bad legal drafting causes inappropriate or less appropriate legislation, and how the non-using the right legal drafting technique contributes to the final impression that the legislation is bad, complicated and incomprehensible. Some of the examples, described in this article, prove that the poorly prepared regulations cause trouble in the interpretation and/or their meaning is different than preliminary estimated.
Keywords: nomotehnika; pravno normiranje; zakonodaja; zakonodajni postopek